Pengaruh Return on Equity, Debt to Equity Ratio, Fixed Asset Turnover, Price to Book Value dan Interest Rate terhadap Price Earning Ratio pada Perusahaan Property & Real Estate di Bursa Efek Indonesia - Agung Setiyawan; Oman Rusmana (Jurnal Riset Akuntansi & Perpajakan (JRAP), 2014)
ABSTRACT This study is aimed to examine the influence return on equity (ROE), debt to equity ratio (DER), fixed assets turnover (FATO), price to book value (PBV) and interest rate (IR) towards price earning ratio (per). Population of this study are Property & Real Estate companies which had go public in Indonesia Stock Exchange (IDX) during the period of 2008-2012.This research take 11 samples of 52 Property & Real Estate companies listed in IDX during the period of 2008-2012. This research concluded that the price to book value (PBV) and interest rate (IR) have significant influence towards the price earning ratio (PER). Meanwhile, other variables partially have no significant influence towards the price earning ratio (PER). ABSTRAK Penelitian ini dilakukan untuk menguji pengaruh return on equity (ROE), debt to equity ratio (DER), fixed assets turnover (FATO), price to book value (PBV) dan interest rate (IR) terhadap Price Earning Ratio (PER). Populasi penelitian adalah perusahaan-perusahaan Property & Real Estate yang terdaftar di Bursa Efek Indonesia (BEI) selama periode 2008-2012. Penelitian ini mengambil jumlah sampel sebanyak 14 perusahaan dari 52 perusahaan Property & Real Estate yang terdaftar di BEI selama periode 2008-2012. Hasil penelitian menunjukkan bahwa variabel Price to Book Value (PBV) dan Interest Rate (IR) secara parsial berpengaruh signifikan terhadap Price Earning Ratio (PER). Sedangkan Return on Equity (ROE), Debt to Equity Ratio (DER) dan Fixed Assets Turnover (FATO) tidak berpengaruh signifikan terhadap Price Earning Ratio (PER). JEL Classification: G14, G30